On the determination of transportation, range and distribution characteristics of Uranium-238, Thorium-232 and Potassium-40: a critical review - Kulahci, Fatih; Cicek, Serif (Springer, 2019)
This research presents the theoretical and experimental results in real time and suggests spatial models after reviewing the spatial modelling method, which has an important place in earth sciences. It also reveals the geological and geophysical descriptions of mathematical models, calculations and the ease with which one can interpret the results. U-238, Th-232 and K-40 concentrations are determined in water and bottom sediment samples taken from Keban Lake as a sample study area. The point cumulative semi-variogram (PCSV) method application helps to identify the range, distribution and transport of radionuclide at each sampling station. The well-known semi-variogram (SV) is used in many scientific studies. In this study, the SV methodologies are reviewed leading to the application of the PCSV method for the real-time data. The radionuclide distributions in the lake are revealed by means of ten regional models. In addition, iso-radioactivity maps are obtained to provide an overview of the medium radioactivity with characterizations of the transport, range and distribution of the three radionuclides in the lake.
Keywords: Spatial modelling; Radionuclide transport in water; Radionuclide range in soil; Behaviours of radionuclides in nature